"Tell me more about this…": An examination of the efficacy of follow‐up open questions following an initial account. Issue 5 (24th April 2020) - Kontogianni, Feni; Hope, Lorraine; Taylor, Paul J.; Vrij, Aldert; Gabbert, Fiona
Summary: In information gathering interviews, follow‐up questions are asked to clarify and extend initial witness accounts. Across two experiments, we examined the efficacy of open‐ended questions following an account about a multi‐perpetrator event. In Experiment 1, 50 mock‐witnesses used the timeline technique or a free recall format to provide an initial account. Although follow‐up questions elicited new information (18–22% of the total output) across conditions, the response accuracy (60%) was significantly lower than that of the initial account (83%). In Experiment 2 ( N = 60), half of the participants received pre‐questioning instructions to monitor accuracy when responding to follow‐up questions. New information was reported (21–22% of the total output) across conditions, but despite using pre‐questioning instructions, response accuracy (75%) was again lower than the spontaneously reported information (87.5%). Follow‐up open‐ended questions prompt additional reporting; however, practitioners should be cautious to corroborate the accuracy of new reported details.